(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
For design purposes, it`s necessary to know the compression rate of soil layers which might be happened when it`s subjected to effective stresses. Also, it`s essential to know the rate of flow through soil mass specially for the design of marine structures or earth embankment. These two important behavior could be predicted from the coefficient of consolidation (Cv) and the coefficient of permeability (k). This study shows the effect of cutback asphalt stabilization on Cv and k and other compressibility factors, the investigation was done for silty clay samples, specimens were prepared by mixing the soil with different percentage of asphalt from (0-10)% and subjected to one-dimensional consolidation test of 50mm diameter and 20mm height were done at soaked condition, it was conducted that Cv increased for asphaltic soil of (2-6)% Cutback and decreased for soil with cutback of (8-10)%. On the other hand, the the coefficient of permeability (k) and the coefficient of volume change (mv) increased for soil with (2-4)% cutback and decreased by adding more cutback asphalt to soil till 10%. The compression index (Cc) value increase to the optimum value at 2% cutback content then start to decrease till reaching the 10%. The re-compression index (Cr) shows a general increase in values when add cutback asphalt to the soil, it increase until reaching its maximum value at 6% cutback content then decrease with increasing of cutback asphalt till 10%, the values of (Cr) shows an increase for the 10% cutback from 8%, that’s might be due to increasing of swelling potential due to increasing of liquid limit and blocking of voids ratio.